Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques

Ce sexe qui n'en est pas un - Irigaray, Luce (Collection Critique, 1977)
Comment parler de l’autre côté, se demanda Alice. Car, en fait de merveilles, elle avait découvert qu’elle était plus d’une, et qu’une seule langue ne pouvait signifier ce qui avait lieu entre elles. Il fallait pourtant essayer de se faire entendre. Alors, s’appliquant, elle reprit : Que dire d’une sexualité féminine autre ? Autre que celle prescrite dans et par l’économie du pouvoir phallique. Autre que celle encore et toujours décrite – et normalisée – par la psychanalyse. Comment inventer, ou retrouver, son langage ? Comment interpréter le fonctionnement social à partir de l’exploitation des corps sexués des femmes ? Que peut être, dès lors, leur action par rapport au politique? Doivent-elles ou non intervenir dans les institutions ? Par quel biais échapper à la culture patriarcale ? Quelles questions poser à son discours ? À ses théories ? À ses sciences ? Comment les énoncer pour qu’elles ne soient pas, à nouveau, soumises à la censure ou au refoulement ? Mais aussi : comment déjà parler femme ? En retraversant le discours dominant. En interrogeant la maîtrise des hommes. En parlant aux femmes, entre femmes. Questions – parmi d’autres – qui s’interrogent et se répondent dans plusieurs langues, sur plusieurs tons, à plusieurs voix. Déconcertant l’uniformité d’un discours, la monotonie d’un genre, l’autocratie d’un sexe. Innombrables les désirs des femmes, et jamais réductibles à l’un ni à son multiple. Le jour était déjà levé depuis longtemps. Une histoire n’en finissait pas d’imposer son ordre. De l’obliger à s’exposer dans une clarté un peu froide. Dans l’attente d’un autre matin, elle repassa derrière le miroir, et elle se retrouva entre elles toute(s). Luce Irigaray
Keywords: 1900-1999; 1970-1979; corps; cours; cycles supérieurs; différence des sexes; discipline; europe; fem1000; fem7000; france; har4600; langage féminin; lit3220; premier cycle; psy4910; psychanalyse; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; sexualité féminine; thématiques; écriture des femmes*